2021
DOI: 10.3390/rs13142774
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Spatial and Temporal Patterns of Liana Infestation Using Satellite-Derived Imagery

Abstract: Lianas (woody vines) play a key role in tropical forest dynamics because of their strong influence on tree growth, mortality and regeneration. Assessing liana infestation over large areas is critical to understand the factors that drive their spatial distribution and to monitor change over time. However, it currently remains unclear whether satellite-based imagery can be used to detect liana infestation across closed-canopy forests and therefore if satellite-observed changes in liana infestation can be detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 63 publications
2
6
0
Order By: Relevance
“…Our results indicated that green and shortwave infrared wavelength regions were especially important for detecting the ferns and vines within the dense vegetation of tropical rainforests (Figure 5). This result is consistent with the previous reports that showed the potential of the visible green wavelength or shortwave infrared region to separate liana or fern from trees [21,[23][24][25][26]28,77]. On the other hand, the individual near-infrared wavelength region was less important, but vegetation indices calculated based on near-infrared regions with green (NDWI) or SWIR2 (NBR) were effective.…”
Section: The Important Variables For Detecting the Fern-vine Continuu...supporting
confidence: 92%
See 3 more Smart Citations
“…Our results indicated that green and shortwave infrared wavelength regions were especially important for detecting the ferns and vines within the dense vegetation of tropical rainforests (Figure 5). This result is consistent with the previous reports that showed the potential of the visible green wavelength or shortwave infrared region to separate liana or fern from trees [21,[23][24][25][26]28,77]. On the other hand, the individual near-infrared wavelength region was less important, but vegetation indices calculated based on near-infrared regions with green (NDWI) or SWIR2 (NBR) were effective.…”
Section: The Important Variables For Detecting the Fern-vine Continuu...supporting
confidence: 92%
“…Matongera et al [22] have demonstrated the possibility of mapping the distribution of bracken fern (Pteridium spp.) thickets by using Landsat 8 imagery, and Chandler et al [23] have mapped the vine-laden forest by using the Sentinel-2 imagery of Bornean tropical rainforests. However, no study has classified both vegetation types, which together threaten forest recovery, within the same landscape.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To make remote sense of lianas, different combinations of sensors and platforms are (to be) used. For example: Spatial and temporal liana distributions (section 2) can benefit from Sentinel‐2 satellite data (Chandler, van der Heijden, Boyd, & Foody, 2021; see panel [a]) and airborne hyper‐spectral and LiDAR data (e.g. Chandler, van der Heijden, Boyd, Cutler, et al, 2021; see [b]).…”
Section: Introductionmentioning
confidence: 99%